Retrospective Analysis of Child Forensic Cases Admitted to the Pediatric Emergency Department of Tepecik Training and Research Hospital and Consulted with Orthopedics and Traumatology - Can Doruk Basa; Melikşah Uzakgider; İsmail Eralp Kaçmaz; Vadym Zhamilov; Gökçe Karaman; Oğuzhan Ekizoğlu; Haluk Ağuş (Galenos Yayinevi, 2021)
Introduction:In this study, we aimed to reveal the demographic data and the trauma characteristics of the patients with orthopedic trauma, which is common in childhood.Methods:In our study, 117 forensic cases aged 0-18 years, who applied to the Pediatric Emergency Department of University of Health Sciences Turkey, Tepecik Training and Research Hospital between 01.01.2016 and 31.12.2016, were consulted to the orthopedics and traumatology. The demographic characteristics of the patients, the way of applying to the emergency service, the type of trauma, the characteristics of the injury that occurred, additional consultations required from other clinics, radiological imagings other than direct radiography, and hospitalization of the patients were evaluated.Results:35.9% (n=42) of the patients included in our study were girls and the average age of girls were 9.09 (±6.04) years, and the average age of boys were 11.82 (±5.05) years. It was observed that the most common injury region was upper limbs with 52.1%. There was an increase in the number of blunt traumas, penetrating device injuries and gunshot injuries at older ages. It was observed that 45.3% (n=53) of the patients were consulted to other clinics besides the orthopedics and traumatology. When the patients were consulted, it was seen that they were consulted predominantly for surgical branches, especially neurosurgery (n=38, 32.4%) and pediatric surgery (n=28, 23.9%).Conclusion:In the majority of the forensic cases in children age group who are in need of orthopedics and traumatology consultation in the emergency department, injury occurs as a result of falling from height. Especially after the age of 14 years, it was seen that blunt trauma and sharp object injuries came into prominence in forensic cases related to orthopedics and traumatology clinic.